METODE PENELITIAN STUDI KASUS DALAM PENDEKATAN KUALITATIF - Nyangfah Nisa Septiana; Zulfatul Khoiriyah; Shaleh (STKIP Subang, 2024)
Qualitative research plays an important role in understanding complex social phenomena, providing deep insights that cannot be achieved through quantitative approaches. This article examines the case study method as one type of qualitative research that is effective for exploring certain issues. The research method used is literature. Data collection techniques include documentation and searching for variables such as records, books, journals, newspapers, magazines, and so on. The data analysis techniques used are collection, condensation, presentation, and drawing conclusions from the data obtained. The results showed that the case study method can reveal the dynamics and complexity of the phenomenon under study, as well as provide a better understanding of the social context. The implications of this research emphasize the importance of applying the case study method in social and educational research, as well as the need for researchers to pay attention to the limitations and challenges that may be faced in the research process. As such, case studies can be a valuable tool in expanding our understanding of various social phenomena.